Programmed death-ligand 1 (PD-L1) expression in Hodgkin’s lymphoma among Peruvian patients - Villa Robles, María del Rosario (2022)
Objective: Various studies on Hodgkin’s lymphoma (HL) have determined programmed death-ligand 1 (PD-L1) expression in Hodgkin and Reed-Sternberg (HRS) cells, with variable results. This protein has gained relevance for its role in theimmune response in malignant neoplasms. This work aimed to determine PD-L1 immunohistochemical expression in HRS cells and its relationship with age, sex, clinical stage and overall survival (OS) in a cohort of Peruvian patients. Materials and methods: Twenty-five (25) biopsies from patients diagnosed with HL were assessed, which allowed determining PD-L1 immunohistochemical expression in HRS cells in relation to OS and clinical data of the patients. Results: All cases showed PD-L1 expression in more than 1 % of tumor cells. There was no statistically significant difference in OS when two groups were compared in terms of PD-L1 expression with a cut-off point of 50 %, clinical stage (CS), age and sex. Conclusions: High PD-L1 expression was found in pre-treatment HL tumors. No association was found between PD-L1 expression, OS, age, sex or CS. Further studies with a larger number of patients are necessary to reassess the prognosticimpact of the expression of this protein in HL.